2022
DOI: 10.1111/cas.15429
|View full text |Cite
|
Sign up to set email alerts
|

A tumor metastasis‐associated molecule TWIST1 is a favorable target for cancer immunotherapy due to its immunogenicity

Abstract: Although neoantigens are one of the most favorable targets in cancer immunotherapy, it is less versatile and costly to apply neoantigen‐derived cancer vaccines to patients due to individual variation. It is, therefore, important to find highly immunogenic antigens between tumor‐specific or associated antigens that are shared among patients. Considering the cancer immunoediting theory, immunogenic tumor cells cannot survive in the early phase of tumor progression including two processes: elimination and equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Yuki Yajima et al also found that twist1 is a promising target for immune-based cancer treatment due to its association with highly immunogenic antigens. [ 16 ] Based on these evidence, we propose that twist1 could be a critical target for understanding tumor development, progression, and potential immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuki Yajima et al also found that twist1 is a promising target for immune-based cancer treatment due to its association with highly immunogenic antigens. [ 16 ] Based on these evidence, we propose that twist1 could be a critical target for understanding tumor development, progression, and potential immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] There have also been advancements in twist1-related vaccines to improve immunotherapy against a broad range of twist1-expressing tumors. [ 16 , 17 ] These findings suggest that twist1 is a highly immunogenic shared antigen and a promising target for cancer immunotherapy. However, a comprehensive analysis of the landscape of twist1 in pan-cancer is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate acid phosphatase, a TAA with high expression levels in prostate cancer cells, is the target of this therapeutic strategy. [57][58][59] T A B L E 1 Current therapeutic options for triple-negative breast cancers based on Phase III clinical trials. 47 in numerous studies to trigger antigen-specific T lymphocytes and generate good antitumor effectiveness.…”
Section: Taamentioning
confidence: 99%
“…Pulmoneucel‐T, the first authorized autologous dendritic cell vaccination, is an example of a successful treatment that can increase lifespan in patients with metastatic resistant prostate cancer by two to 4 months. Prostate acid phosphatase, a TAA with high expression levels in prostate cancer cells, is the target of this therapeutic strategy 57–59 . Furthermore, in patients with incurable melanoma, an mRNA vaccination containing four TAAs has shown the ability to stimulate strong and long‐lasting immune responses versus such antigens.…”
Section: Optimal Tumor Antigen Selection In Cancer Vaccinementioning
confidence: 99%
“…On the other hand, tumor antigens can also be categorized as per their peculiar expression characteristics [ 29 ]. Some of the relevant classes in this regard include cancer/testis antigens (CTA) , which are restricted to reproductive organs (testis and placenta) but are overexpressed by cancer cells; oncoviral antigens , encoded by tumorigenic viruses and, thus, found only on virus-infected tumor cells; overexpressed/differentiation antigens , which are found in normal tissues but are significantly overexpressed in cancer cells; and mutated antigens (also known as neoantigens ), unique tumor antigens generated by a genetic mutation or alteration in transcription and found only in cancer cells [ 29 , 30 , 31 ]. Some of the prominent tumor antigens that have contributed greatly to the development of therapeutic vaccines, particularly in HNSCC, are the melanoma antigen-encoding gene (MAGE) ( CTA ), HPV-E6, E7 ( oncoviral ), Epstein–Barr virus (EBV)-related latent membrane protein (LMP)-2 ( oncoviral ), MUC-1, Wilm’s tumor (WT)-1, survivin, carcinoembryonic antigen (CEA) ( overexpressed and SHA ), and epidermal growth factor receptor(EGFR)-vIII (neoantigen ) [ 32 ].…”
Section: Basic Principles Of Therapeutic Vaccinesmentioning
confidence: 99%